Transcripter-Generation of the transcript from audio to text using Deep Learning - Ansari, Fatima; Gupta, Ramsakal; Singh, Uday; Shaikh, Fahimur (International Journal of Computer Sciences and Engineering, 2019)
A video is the most powerful medium in the propagation of information and important part of the video for exchanging the information is audio, which is an important aspect of the video on which the whole message depends and as it is used in all field like Teaching, Entertainment, Conference Meeting, News Broadcast. So converting the Audio into Text in Documented format make easy for referring purpose as it is difficult to search the said word in the video as compared to the transcript. The main objective of developing this system is to present an automated way to generate the transcript for audio and video. As it is not possible to make the same informative video in all Languages. So this the place where our System plays an important role. It will extract the audio from the given video and transcript is generated based on which it can be translated into any desired language. It can be very useful for people who speak the language which is not used by the majority of the population. In this way, it has much application in all field where information exchange is happening based on Video.